Prototype of Water Quality Monitoring for Grouper Fish Pond Based on Microcontroller Arduino - Rizal, Fahrul; Santyadiputra, Gede Saindra; Pradnyana, Gede Aditra (International Journal of Natural Science and Engineering, 2021)
Prototype monitoring of grouper pond water quality is intended to improve the water quality of grouper ponds if there is a change in air quality such as acidity, air temperature, and air turbidity level, which can be caused by fish or fish that can be used on fish breathing fish that can make fish become stressful and cannot multiply properly and can cause death in fish. To overcome these problems, a technology that can be studied and controlled according to the standards is needed. It can also facilitate pond farmers to facilitate pond air quality and the automation of standardization of water quality indicators. This development uses internet-related matters in data communication between prototypes with farm farmers. The development model used is prototyping. For the testing process, (3) trials are conducted: (1) evaluation testing, with test results, prototypes, get a percentage of 100% with a very effective category. (2) validity testing, with a margin of error of 4.38% and the overall sensor test results under 4.38%. (3) practically test, obtained by the results of 92.2% of respondents stated that monitoring of this prototype is very practical.